Leves of family satisfaction and communication between parents and children - Sobrino Chunga, Lisle (2008)
This is a descriptive research, ex post-fact design, with a sample of 1300 university students ( men and women), aged between 16 and 30 years, from general studies from 7 peruvian universities. The instrument applied was The family satisfaction scale, by Olson and Wilson.